1999
DOI: 10.1016/s0006-3495(99)77228-0
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Chemotactic Cell Sorting during Dictyostelium discoideum Mound Formation

Abstract: Coordinated cell movement is a major mechanism of the multicellular development of most organisms. The multicellular morphogenesis of the slime mould Dictyostelium discoideum, from single cells into a multicellular fruiting body, results from differential chemotactic cell movement. During aggregation cells differentiate into prestalk and prespore cells that will form the stalk and spores in the fruiting body. These cell types arise in a salt and pepper pattern after what the prestalk cells chemotactically sort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 33 publications
2
45
0
Order By: Relevance
“…In reality, Dictyostelium cells do not move at a constant speed. For example, it has been shown that in Dictyostelium discoideum aggregations, cells speed depends on the chemoattractant and on its spatial and temporal gradients [17,20,34,35]. The cells also speed-up or slow-down as a consequence of cell-cell mechanical interactions or interactions with the substratum and the so-called slime sheath that surrounds the slug [38].…”
Section: Summary and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In reality, Dictyostelium cells do not move at a constant speed. For example, it has been shown that in Dictyostelium discoideum aggregations, cells speed depends on the chemoattractant and on its spatial and temporal gradients [17,20,34,35]. The cells also speed-up or slow-down as a consequence of cell-cell mechanical interactions or interactions with the substratum and the so-called slime sheath that surrounds the slug [38].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…One can observe the cAMP pulses propagating from the centre, with a period of approximately 7.5 minutes. In reality, PSP and PST cells differ in many aspects: PST cells are faster (stronger chemotactic forces), more excitable (produce more cAMP), and less adhesive (lower viscosity) [17,20]. This led us to investigate the case of different speeds, chemotactic sensitivities, and mechanical interactions.…”
Section: (I) Cell Sorting and Cell-type Conversion In Isolated Psp Frmentioning
confidence: 99%
See 3 more Smart Citations